Physical, Chemical Parameters and Saphrobic Coefficients (X) as Determinants of Water Quality in the Senapelan River, Pekanbaru - Siti Ramlah; Nur El Fajri; Adriman ' (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2015)
Senapelan River is one of the polluted river in Pekanbaru. The pollutants in this river are originated from domestic activities, tofu industries and palm oil plantation. To understand the water quality in general, a research was conducted from January to February 2015. This research aims to determine the water quality of the river based on physical, chemical and saphrobic coefficient parameters. There were three stations, 3 sampling points/ station. Water samples were taken 3 times/ week. Water quality parameters measured were temperature, turbidity, brightness, current speed, total suspended solid, depths, pH, DO, BOD5, nitrate, phosphate and types of plankton present. Results shown that there were 7 classes of plankton present, namely Cyanophyceae (4 species), Chlorophyceae (9 species), Bacillarophyceae (1 species), Xantophyceae (1 species), Euglenophyceae (8 species), Rotifers (1 species) and Ciliate (3 species). Water quality parameters are as follows : Temperature 27-280C, turbidity 20.67-50 NTU, brightness 8-11.67 cm, current speed 3.19-7.36 cm/s, TSS 5.67-15 mg/L, depths 17-138 cm, pH 6-7, dissolved oxygen 2.3-5.23 mg/L, BOD5 4.8-12.37 mg/L, nitrate 0.11-0.89 mg/L and phosphate 1.47-2 mg/L. The value of WQI-NSF index of the Senapelan River was 24-31, indicates that this river is badly polluted. The Saphrobic Coefficient shown that the saphrobic phase of the river is is α/β- mesosaphrobic to α- mesosaphrobic, indicates that the pollution level of the river is medium to heavy polluted.Keywords : Senapelan River, Water Quality, Saphrobic Coefficient